Pengaruh Pembelajaran Open Ended Berbantuan Google Classroom Terhadap Kemampuan Pemahaman Konsep Matematis Siswa Junior High School Negeri 1 Bilah Hilir - Yani Sahara Hutasuhut; Ani Minarni (Pusdikra Publishing, 2023)
The purpose of this study is to determine and describe the effect of open ended learning with the help of gooole classroom on the ability to understand mathematical concepts of students of Junior High School Negeri 1 bar Hilir. The population in this study is the entire class VIII Junior High School Negeri 1 bar Hilir which consists of 7 classes whose total number of students is 145 students. While the sampling in the study as suggested by the teacher is Class VIII-3 as an experimental class and VIII-4 as a control Class of 15 students. As a research instrument, pre-test and post-test result data is used in the form of essay test on Relation and function material, where each question is 4 questions and has been validated by mathematics lecturer. The test used in this study is the Right t-test. After the management of statistical data t-test the right party obtained that tcount = 2,006 dan ttable = 1,70 then tcount > ttable or 2,006 > 1,70. This means accepting Ha dan decline H0 Based on the results of the t-test, it can be concluded that there is an effect of the use of open ended learning approach assisted by google classroom on the understanding of mathematical concepts of Junior High School Negeri 1 bar Hilir students.